PID Controller-Based Closed-Loop Fast Charging of Lithium-Ion Batteries Using the CCCV Method - Tole Sutikno; Tri Wahono; Ahmad Raditya Cahya Baswara (Jurnal Elektronika dan Telekomunikasi, 2025)
This paper presents a closed-loop fast charging system for lithium-ion batteries based on the Constant-CurrentConstant-Voltage (CCCV) method enhanced with a ProportionalIntegralDerivative (PID) controller. The proposed system dynamically regulates the charging parameters by using real-time feedback from voltage and current sensors, with the aim of improving the efficiency of the charging and ensuring battery safety. Experimental results demonstrate that the PID-controlled method maintains a higher current during the initial bulk charging phase, significantly reduces total charging time, and avoids harmful voltage overshoot. Compared to conventional CCCV charging, the system achieves more stable voltage regulation and gradual current tapering, effectively minimizing thermal stress and preventing overcharging. A comparative analysis shows that the PID approach outperforms traditional methods in terms of energy efficiency, thermal management, and operational safety. The system architecture is suitable for integration into Battery Management Systems (BMS) of electric vehicles, portable electronics, and renewable energy storage. This research not only validates the practicality of using PID in fast charging applications but also lays the foundation for future enhancements using intelligent control strategies and adaptive learning algorithms. The findings suggest that PID-controlled charging systems offer a promising solution to the challenges of rapid, reliable, and safe energy replenishment in modern battery-powered technologies.